Cars—a new perspective to hcmv treatment - Bednar, Christopher; Enßer, Armin (Viruses, 2021)
Human cytomegalovirus (HCMV), by primary infection or reactivation, represents a great risk for immune-suppressed or compromised patients. In immunocompetent humans, the immune system suppresses the spread of HCMV during an infection, resulting in a mostly asymptomatic or mild course of the disease, whereas in immune suppressed patients, the compromised host immune response cannot control the viral infection. Multiple viral immunomodulatory mechanisms additionally contribute to immune evasion. Use of chimeric antigen receptors (CARs), a treatment strategy adapted from cancer immunotherapy, is investigated for possible application to combat HCMV and other infections in immunocompromised patients. The administration of CAR+ T-cells directed against HCMV antigens can bypass viral immune evasion and may complement existing treatment methods. This review gives a short overview of HCMV, the obstacles of current treatment options as well as a brief introduction to CARs and the current research situation on CAR+ T-cells against HCMV.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Adoptive T-cell therapy; Antiviral immunotherapy; Chimeric antigen receptor (CAR); Cytotoxic T-lymphocytes; Human cytomegalovirus (HCMV)